Epinephrine delivery via EpiPen® Auto‐Injector or manual syringe across participants with a wide range of skin‐to‐muscle distances. Issue 1 (10th June 2020) - Worm, Margitta; Nguyen, DucTung; Rackley, Russ; Muraro, Antonella; Du Toit, George; Lawrence, Tracey; Li, Hong; Brumbaugh, Kurt; Wickman, Magnus
Abstract: Background: Intramuscular (IM) injection of epinephrine (adrenaline) at the mid‐anterolateral (AL) thigh is the international standard therapy for acute anaphylaxis. Concerns exist regarding implications of epinephrine auto‐injector needles not penetrating the muscle in patients with greater skin‐to‐muscle‐distances (STMD). Methods: This open‐label, randomized, crossover study investigated pharmacokinetics and pharmacodynamics following injection of epinephrine in healthy volunteers. Individuals were stratified by maximally compressed STMD (low, < 15 mm; moderate, 15–20 mm; high, > 20 mm). Participants received epinephrine injections via EpiPen ® Auto‐Injector (EpiPen; 0.3 mg/0.3 mL) or IM syringe (0.3 mg/0.3 mL) at mid‐AL thigh or received saline by IM syringe in a randomized order. Eligible participants received a fourth treatment (EpiPen [0.3 mg/0.3 mL] at distal‐AL thigh). Model‐independent pharmacokinetic parameters and pharmacodynamics were assessed. Results: There were numerical trends toward higher peak epinephrine concentrations (0.52 vs 0.35 ng/mL; geometric mean ratio, 1.40; 90% CI 117.6–164.6%) and more rapid exposure (time to peak concentration, 20 vs 50 min) for EpiPen vs IM syringe at mid‐AL thigh across STMD groups. Absorption was faster over the first 30 min for EpiPen vs IM syringe (partial area under curve [AUC] over first 30 min: geometric mean ratio, 2.13; 90% CI 159.0–285.0%). Overall exposure based on AUC to the last measurable concentration was similar for EpiPen vs IM syringe (geometric mean ratio, 1.13; 90% CI 98.8–129.8%). Epinephrine pharmacokinetics after EpiPen injection were similar across STMD groups. Treatments were well tolerated. Conclusions: Epinephrine delivery via EpiPen resulted in greater early systemic exposure to epinephrine vs IM syringe as assessed by epinephrine plasma levels. Delivery via EpiPen was consistent across participants with a wide range of STMD, even when the needle may not have penetrated the muscle. Trial registrations This trial was registered with the German Clinical Trials Register (DRKS‐ID: DRKS00011263; secondary ID, EudraCT 2016‐000104‐29) on 23 March 2017.